Metoda Rezolucji i Tablice Analityczne w Symbolic Logic Lewisa Carrolla - Pogonowski, Jerzy (Investigationes Linguisticae, 2008)
We discuss Lewis Carroll’s invention of the rule of resolution and his prototype of the analytic tableaux method from 1896. A few examples are analyzed and a modest open problem is formulated. We conclude the paper with some metalogical and historical remarks.1